Assessment of concentration and distribution of total mercury and polychlorinated biphenyls in Green Bay, Wisconsin, USA - Marcia R. Silva; Alice Lecus; Chad Haehle; David Garman; Shelby Brunner (Environmental Science and Pollution Research, 2022)
Under the 1987 Great Lakes Water Quality Agreement, the lower Green Bay and Fox River estuary have been labeled as areas of concern due to the contamination of mercury and polychlorinated biphenyls (PCBs) from industrialization. These pollutants pose substantial health and environmental hazards for the Green Bay region. The PCBs reported in this region, including Aroclor 1242, are known to trigger carcinogenic responses in animals and mercury targets the central nervous system and vital organs. Furthermore, these compounds are extremely difficult to remove from the environment once introduced. Extensive remedial actions have been implemented including dredging sediments in the Lower Fox River from DePere to Green Bay. The purpose of this study is to assess the concentration and distribution of Aroclor 1242 and total mercury in the Green Bay region sediments and pore waters and to assess the impact of interventions and the natural rates of change previously found.